Preparation and electrochemical performances of porous polypyrrole film by interfacial polymerization. Issue 4 (17th May 2012) - Shen, Mingxia; Han, Yongqin; Lin, Xiaochen; Ding, Bing; Zhang, Luojiang; Zhang, Xiaogang
Abstract: In this study, porous polypyrrole (PPy) film was synthesized by facile interfacial polymerization using ionic liquid as oxidant. The morphology of PPys changed from dense microspherical/nanospherical agglomerated structure to porous structure with the increasing concentration of the oxidant. The magnetic ionic liquid, 1‐butyl‐3‐methylimidazolium tetrachloroferrate (Bmim[FeCl4 ]), played a major role of oxidant when the concentration was lower than 0.075 M . As the concentration increased to 0.075 M, the π–π interactions between pyrrole cations and iminazole ring of Bmim[FeCl4 ], as evidenced by Fourier transform infrared spectrometer results, may affect the packing of PPy chains and subsequently cause the formation of porous structure of PPys. Electrochemical performances showed that PPy with porous structure displayed the highest specific capacitance of 170 F/g at a current density of 2 A/g in 1 M H2 SO4 solution and a good capacitive behavior, which has potential application as supercapacitor materials. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :